Analisis Efisiensi Turbin pada Pembangkit Listrik Tenaga Minihydro (PLTM) Malea di Kabupaten Tana Toraja - Jumadi Tangko; Yiyin Klistafani; A Khayrunnisa; Reza Risaldi Robby (Jurnal Teknik Mesin Sinergi, 2019)
Malea Minihydro Power Plant in Tana Toraja district is the only one power plant that supplies electricity directly to Malea Hydropower Project. This analysis provides an explanation or description of the circumstances of power plant under study ranging from waterways to the performance of Francis turbine. Aims to find out the efficiency that produced by turbine and factors that influence the turbine efficiency. In this research, the turbines studied were unit 1 and unit 2. Data obtained from measurement results and annual data of Malea Minihydro Power Plant with documentation. The results showed that every year there was a decreasing in turbine efficiency both in unit 1 and unit 2. This is caused by the reduced performance of some components of turbine. As for the turbine unit 1 the largest turbine efficiency value in 2012 is 98.40%, turbine efficiency value in 2016 is 83.30%, and smallest turbine efficiency value in 2018 is 79.37%. On turbine unit 2 the largest turbine efficiency value in 2012 is 97.46 % and the smallest turbine efficiency value in 2016 is 77.35 %. In 2017 and 2018 turbine unit 2 no longer operate due to damaged bearing. The result showed that efficiency value of Malea MiniHydro Power Plant Tana Toraja less efficient in generating electricity. This is caused by the PLTM have been operated since 2012 and there was no maintenance that done regularly.